Optimasi Jaringan Microwave Link 4G Point To Point Benai-Teluk Kuantan Provider Indosat - Rahmat Maulana; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This paper describes the condition of Indosat's 4G microwave link network in the Benai-Teluk Kuantan area using pathloss software. Microwave link functions to transmit information from one place to another without any interference. PT. Xerindo Teknologi is a company that provides services through the internet network of all providers including Indosat. The design carried out by PT. Xerindo Teknologi simulated with Pathloss software to experience some obstacles such as trees and buildings. These caused a nonoptimal network, with a network speed of around 2-3 Mbps from the speedtest results. To enhance the microwave link network conditions in the Benai-Teluk Kuantan area, the solution will be to change the antenna height that has been done previously. Changing the antenna height results in optimal network speed, with a network speed of around 7-8 Mbps. .Keywords: Microwave link, 4G Technology, Network planning and network optimization.